Evaluating Sustainability:: Limits and Possibilities in Alto Douro Vinhateiro, Portugal - Ferreira, José Francisco (Sustainability in Debate, 2013)
The Alto Douro Wine Region, located in North of Portugal, is one of the most important portuguese wine regions. In last decades, it has faced serious difficulties, common to many rural areas of the country and around the world. Problems such as aging and population loss, low economic, social and cultural density, low literacy, difficulties in the wine sector, poor associative movement, lack of common strategies among regional municipalities, and institutional difficulties, among others, affect its development and suggest that the region may not be managed in a sustainable way. Facing this scenario, a methodology to assess regional sustainability was developed. 76 indicators were used, grouped into 23 aspects and 5 dimensions. From this evaluation, a regional value was obtained which translates the regional situation relating to sustainable development. In a 0 to 100 scale, the region received a score of 57.14 points, showing that sustainability, if implemented as a regional strategy, could be highly benefic to regional improvement.